THE ‘AMERICAN’ HEGEMONIC CULTURE: ITS ROOTS, FEATURES AND IMPLICATIONS TO WORLD CULTURE - Kasiyarno Kasiyarno (Universitas Gadjah Mada, 2014)
That America is historically a nation which developed a hegemonic culture around the world has been an unquestionable issue for many Americanists. In that kind of culture, it insisted that the world had no alternative but acceptance of American ideas, values and way of life. This is what we call as Americanization which drives a cultural imperialism through eagerly practicing the hegemonic culture primarily when the country rose as the single world hegemon. It is really factual that American hegemonic culture is the cultural heritage from British Empire, which had already got a strong influence from Roman Empire. Because of the strong myth as the chosen people, the United States is clearly identified as a strong expansionist which always tries to control others and acts unilateraly. Through this way, the United States promotes itself as the most influential country and its culture as the most widely imitated around the world.